Long-term management effects on depth gradients of 13C, 15N and C/N ratio in agricultural soils - Laura E. Skadell; Florian Schneider; Sara L. Bauke; Wulf Amelung; Axel Don (Geoderma)
Agricultural management practices influence the turnover and residence time of soil organic matter (SOM) and thus can contribute to carbon (C) removal from the atmosphere. However, advanced analytical techniques are needed to disentangle the interlinked processes of SOM stabilisation and destabilisation, as well as its built-up and decomposition. Stable isotopes of C (δ13C) and nitrogen (N; δ15N) as well as the carbon-to-nitrogen (C/N) ratio provide information about the quality and thus origin and turnover SOM. The aim of this study was to quantify the effect of different agricultural management practices (mineral fertilisation, farmyard manure (FYM) application, straw incorporation, crop rotations, liming, irrigation and reduced tillage) on these indicators in topsoil and subsoil. Ten German long-term experiments (LTEs) were sampled down to 100 cm depth. Changes in SOC and N content were assessed as indicators of SOM quantity and changes in δ13C, δ15N and C/N ratios were assessed as indicators of SOM quality. Increases in C and N content were mainly affected in topsoil by mineral fertilisation, FYM, straw and irrigation. Changes in δ13C were limited to crop rotations (+0.62 ‰) and FYM (−0.27 ‰) in topsoil, but liming effects also reached down to 70 cm (−0.46 ‰ on average). Mineral fertilisation reduced the δ15N values in topsoil (−0.12 ‰), while the application of FYM increased them (+0.53 ‰), indicating different N sources. The δ15N values in the subsoil changed due to crop rotations (+0.62 ‰) and reduced tillage (−0.96 ‰). Specific management practices did not change C/N ratios significantly, with the exception of NPK fertilisation in topsoil (−1.32). Variations in SOC and total N content were more than 50 % greater in subsoil than in topsoil, but 13C and 15N did not follow this trend, indicating a decoupling of changes in C and N content and changes in SOM quality. This study revealed challenges in the detection of subsoil effects due to the low SOM content that in some LTEs unexplained large spatial variability in δ15N in subsoil. Since agricultural management practices change 13C, 15N and C/N ratios at least in topsoil, these variations need to be considered in isotope studies.